MODIFIKASI PEMPEK MENGGUNAKAN BAHAN UTAMA IKAN TERI - Surya Aditya Wahyono; Ita Karnita; Sara Rabasari; Dharmawan Sunjata (Akademi Pariwisata NHI Bandung, 2025)
The utilization of anchovies to date is still limited to salting and direct consumption. Therefore, it is necessary to develop and utilize anchovies more widely and not only limited to salting and consumed directly, but need to be developed in making products, one of which is used as raw material for making pempek. With the abundant population of anchovies in Indonesia, high production value, low price and distinctive savory taste and long shelf life compared to other fresh fish raw materials, researchers are interested in conducting this research in order to make product innovations and utilize highly nutritious local food sources by modifying anchovies as the main basic ingredient in making pempek so as to create different products and have their own advantages to compete in the market. The purpose of this study was to replace the main ingredient of fish, namely Tenggiri fish in making Pempek by using anchovies. Overall, the experimental pempek using anchovies is the most affordable product in terms of total production price and production price per serving, making it a more cost-effective alternative without sacrificing the same packaging quality as the comparison pempek. Keywords: Pempek, Mackarel,Anchovy